Transformation Strategy of Religious Study Program Curriculum Through Industrial Practitioner Engagement to Enhance Graduate Relevanc - Husnul Anwaril Anam (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy article examines the urgency of curriculum transformation within religious study programs at Universitas Islam Negeri Sunan Ampel Surabaya to respond to the ever-changing dynamics of the professional world. The primary issue identified is a competency gap between academic outputs and industrial needs due to rigid curriculum governance and incidental practitioner involvement. This analysis employs a descriptive qualitative policy methodology utilizing William N. Dunn’s evaluation criteria, encompassing effectiveness, efficiency, adequacy, equity, responsiveness, and technical feasibility. Strategic steps are formulated through problem identification using the Urgency, Seriousness, and Growth method and root cause mapping through a systemic thinking framework. Based on the assessment, five policy alternatives are proposed, focusing on the institutionalization of practitioner roles through the establishment of an Industrial Advisory Board, the implementation of an agile curriculum, and the synchronization of outcome-based learning achievements. This strategy is supported by conceptual frameworks of human capital, constructivism, and the Triple Helix model to ensure a harmonious integration between Islamic values and industrial professionalism. The implementation of this policy is expected to shift the educational paradigm from pure theoretical mastery toward adaptive transversal competency. By strengthening strategic collaboration between the university and the private sector, the institution can ensure that religious study program graduates possess high competitiveness, proficient digital literacy, and readiness to face future global labor market disruptions